2020
DOI: 10.1101/2020.10.23.20218214
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The French Covid-19 contact tracing app: knowledge, attitudes, beliefs and practices of students in the health domain

Abstract: Background: Many countries around the world have developed mobile phone apps capable of supporting instantaneous contact tracing to control the Covid-19 pandemic. In France, a few people have downloaded and are using the StopCovid contact tracing app. Reasons for this low uptake are unexplored. Students in the health domain are especially concerned and their usage and opinions about the app can inform improvements and diffusion of StopCovid among young people. Objective: To investigate health-related students… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…Official figures may overestimate real adoption levels, because many individuals may download the application without using it. In France, this proportion was 60% among university students (53).…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Official figures may overestimate real adoption levels, because many individuals may download the application without using it. In France, this proportion was 60% among university students (53).…”
Section: Discussionmentioning
confidence: 96%
“…Higher levels were observed, e.g., in Australia (6 million downloads, 25% of the population) ( 51 ) and Iceland (~150 thousand, 38%) ( 52 ).Official figures may overestimate real adoption levels, because many individuals may download the application without using it. In France, this proportion was 60% among university students ( 53 ). Individuals may be more inclined to use the app if they perceive a direct and immediate benefit from its use.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An easy system for reporting technical difficulties and a minimally disruptive evaluation of other app functionalities may therefore increase use. Moreover, since one main barrier to app uptake is privacy and data security concerns [ 21 - 23 , 27 , 29 , 49 , 75 , 76 ], users can be empowered by designs that use customizable app functionalities. For example, app users could be offered choices in the technology used to collect the data (GPS or Bluetooth), how the data is stored [ 77 ], and the level of interaction with local health agencies.…”
Section: Discussionmentioning
confidence: 99%
“…An influential modeling study published by a team of researchers at the University of Oxford originally suggested that a 60% adoption rate should be targeted for effective virus transmission reduction, although any level of uptake may help lower disease transmission [ 19 , 20 ]. Even though numerous public consultations have suggested a general willingness to use contact tracing apps during the pandemic [ 21 - 28 ], the available data suggests low rates of continuous use in practice [ 27 , 29 , 30 ]. For instance, app penetration rates as of March 2021 were as low as 3.6% in France, 6.1% in Japan, 14% in Canada, and 28.5% in the United Kingdom.…”
Section: Introductionmentioning
confidence: 99%